MANUFACTURED INCLUSIVITY: A MULTIMODAL DISCOURSE ANALYSIS OF MAD FOR MAKEUP'S INSTAGRAM CAMPAIGN - Amalia Rizki Nur Insani; Muhammad Hafiz Kurniawan (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study examines how inclusivity is constructed through verbal and visual strategies in Mad For Makeup’s #GetPearlFectSkin campaign within the context of Indonesian social media beauty marketing. Using a qualitative multimodal discourse analysis approach, three testimonial videos were purposively selected based on their representation of diverse skin tones. The data were analyzed using Genre Relations Theory, Appraisal Theory, and visual ambience frameworks. The findings reveal a systematic multimodal coordination across the campaign, including an identical three-stage genre structure consisting of context, description, and evaluation. Linguistically, positive attitude dominated the discourse (56%), while negative attitude appeared minimally (1%). In addition, linguistic upscaling frequently occurred (37.93%) to intensify positive evaluations. Visually, the campaign employed a standardized ambience characterized by warm tones (79%) and familiar settings (78%), creating a sense of intimacy and relatability. These patterns suggest that inclusivity in the campaign functions primarily as a manufactured branding strategy rather than an organically emerging practice. Although the campaign provides greater visibility for diverse beauty representations, such inclusivity remains constrained by commercial control. Overall, this study highlights the tension between surface-level diversity and genuine empowerment, contributing to broader discussions on manufactured authenticity in digital beauty marketing.